Analysis of the internal transcribed spacer region of Ascaris suum and Ascaris lumbricoides derived from free range Tibetan pigs. (19th May 2018) - Li, Kun; Luo, Houqiang; Zhang, Hui; Mehmood, Khalid; Shahzad, Muhammad; Zhang, Lihong; Li, Jiakui
Abstract: Ascaris suum ( A. suum ) is the most commonly occurring worldwide internal parasite of pigs; however, little is known about this organism in Tibetan pigs in China. A study was carried to isolate and identify the characteristics of internal transcribed spacer region ( ITS ) gene of A. suum derived from Tibetan pigs. Adult nematodes were collected from Tibetan pigs in 2015–2016. Total genomic DNA of the extracted parasites was performed and a fragment of the ITS of mitochondrial (mt) gene was amplified. The amplicons were cloned into PGEM®-T Easy Vector (Promega, WI) and the positive clones were sequenced by ABI 3730 × 1 sequencer. The sequence and phylogenetic analysis were performed by ClustalWVer. 1.4 and MEGA 6.0 software, respectively. Results indicated that the identity of A. suum isolates was 98.4%–99.9% with previously reported pig isolates, and 99.4%–99.7% with A. lumbricoides isolates. To the best of our knowledge, this is the first report describing the characteristics of ITS gene of A. suum derived from the Tibetan pigs from high and remote areas depicting high identity with the isolates of both A. suum and A. lumbricoides .